Emergency department visits for dog bite injuries in Missouri municipalities with and without breed-specific legislation: a propensity score-matched analysis - Brett Wyker; Maya Gupta (Frontiers Media S.A., 2024)
Breed-Specific Legislation is a type of law that bans or restricts ownership of specific dog breeds. Some local governments - including over seventy municipalities in the state of Missouri - have enacted Breed-Specific Legislation to prevent injuries from dog bites. Several studies from the peer-reviewed literature have found that aggressive behavior is not associated with any particular dog breeds and, since 2018, at least a dozen municipalities in Missouri have repealed these laws. To evaluate the impact of Breed-Specific Legislation on public safety, the 2010-2015 rates of emergency department visits for dog bite-related injuries in Missouri municipalities with and without Breed-Specific Legislation were compared. Propensity-score matched negative binomial regression models were used to assess the effect of breed restrictions on injury rates while balancing the samples on population characteristics and estimates of dog ownership. After matching the sample on population, housing and dog ownership estimates, no association was found between emergency department visits for dog bite injuries and whether the municipality enacted Breed-Specific Legislation. However, the incidence rate ratio of emergency room visits for dog bite-related injuries increased by 13.8% for every 1% increase in the percentage of males aged 5 to 9 in the population (p < 0.01). This study has found breed discriminatory laws have not reduced the risk of emergency department visits for injury from dog bites in Missouri. There appears to be no greater risk to public safety as local governments move to repeal existing breed bans.